Are Three Contact Efforts Really Reflective of a Repeated High-Intensity Effort Bout?. Issue 3 (March 2015) - Johnston, Rich D.; Gabbett, Tim J.; Walker, Shane; Walker, Ben; Jenkins, David G.
Abstract : Abstract: Johnston, RD, Gabbett, TJ, Walker, S, Walker, B, and Jenkins, DG. Are three contact efforts really reflective of a repeated high-intensity effort bout? J Strength Cond Res 29(3): 816–821, 2015—The use of 3 or more efforts (running and contact), separated by short recovery periods, is widely used to define a "repeated high-intensity effort" (RHIE) bout in rugby league. It has been suggested that due to fatigue, players become less effective after RHIE bouts; however, there is little evidence to support this. This study determined whether physical performance is reduced after performing 1, 2, or 3 efforts with minimal recovery. Twelve semiprofessional rugby league players (age: 24.5 ± 2.9 years) competed in 3 "off-side" small-sided games (2 × 10-minute halves) with a contact bout performed every 2 minutes. The rules of each game were identical except for the number of contact efforts performed in each bout. Players performed 1, 2, or 3 × 5-second wrestling bouts in the single-, double- and triple-contact game, respectively. Movement demands of each game were monitored using global positioning system units. From the first to the second half, there were trivial reductions in relative distance during the single-contact game (ES = −0.13 ± 0.12), small reductions during the double-contact game (ES = −0.47 ± 0.24), and moderate reductions during the triple-contact game (ES = −0.74 ± 0.27). These data show that running intensity is progressively reduced as the number of contact efforts per bout is increased. Targeting defensive players and forcing them to perform 2 or more consecutive contact efforts is likely to lead to greater reductions in running intensity. Conditioning performing multiple contact efforts while maintaining running intensity should therefore be incorporated into training for contact team sports.